Can primary care data be used to monitor regional smoking prevalence? An analysis of The Health Improvement Network primary care data - Wythe Stephen; Szatkowski Lisa C; Langley Tessa E; Lewis Sarah A (BMC, 2011)
Abstract Background Accurate and timely regional data on smoking trends allow tobacco control interventions to be targeted at the areas most in need and facilitate the evaluation of such interventions. Electronic primary care databases have the potential to provide a valuable source of such data due to their size, continuity and the availability of socio-demographic data. UK electronic primary care data on smoking prevalence from The Health Improvement Network (THIN) have previously been validated at the national level, but may be less representative at the regional level due to reduced sample sizes. We investigated whether this database provides valid regional data and whether it can be used to compare smoking prevalence in different UK regions. Methods Annual estimates of smoking prevalence by government office region (GOR) from THIN were compared with estimates of smoking prevalence from the General Lifestyle Survey (GLF) from 2000 to 2008. Results For all regions, THIN prevalence data were generally found to be highly comparable with GLF data from 2006 onwards. Conclusions THIN primary care data could be used to monitor regional smoking prevalence and highlight regional differences in smoking in the UK.